Los límites de la investigación traductológica - Campos Plaza, Nicolás (Revista de Investigación Lingüística, 2009)
The disparity among the different translation approaches and the lack of consensus which have characterized the beginning of research on translation makes it rather diffi cult to provide a clear and irrefutable defi nition of the term « translation». The present paper attempts to delimit its object of study by making a clear distinction between translations as such and other phenomena which are placed at the limits of this communicative activity and which should be the object of specific study.